Investigating AI-Driven Collaborative Filtering, Content-Based Filtering, and Hybrid Models for Personalized ProductRecommendations in E-Commerce - M. ROHIT; N. SRINIVASU (Utilitas Mathematica, 2025)
The development of recommendation systems has resulted in their transformation into an essential component of contemporary e-commerce, which has led to an improvement in the user experience and increased engagement. The approaches of collaborative filtering, content-based filtering, and hybrid models are investigated in this study. These are three significant AI-driven methodologies. The collaborative filtering technique is very effective at recognizing patterns in user-item interactions; yet, it is not without its drawbacks, such as the cold-start problem and data sparsity. Personalized recommendations can be generated through the utilization of item attributes through content-based filtering; however, this method challenges with over-specialization and metadata reliance.[3] In order to solve limitations while simultaneously improving accuracy and diversity, hybrid models have developed as a robust alternative. These models integrate the strengths of both conventional and hybrid approaches. Recommendation systems have also been increased due to the fact that there is progress in machine learning, especially deep learning, and this has seen the accumulation of complex user preferences and associations, which are also non-linear. Additionally, the paper explores the challenges and complexities of scalability, the challenge of privacy risks to users, and the need to have systems that are flexible and explainable. Despite these, further studies are required in multi-modal recommendations, reinforcement learning and real time personalization to remain aligned to the evolving needs of e-commerce sites. This paper aims at conducting an in-depth review of these methods, their usage, and the possibilities that these recommendation technologies have in an ever-growing digital landscape of an ecosystem.[5]